Oral health promotion: a multidisciplinary approach - Elaine Alegre Bueno; Rafael Tamborena Malheiros; Rodrigo de Souza Balk (Universidade de Santa Cruz do Sul, 2012)
KEYWORKS Oral health, Family Health, Multidisciplinarity